Learning for universal health coverage - Meessen, Bruno; El Houcine, Akhnif; Kiendrébéogo, Joël (BMJ global health, 2019)
The journey to universal health coverage (UHC) is full of challenges, which to a great extent are specific to each country. ‘Learning for UHC’ is a central component of countries’ health system strengthening agendas. Our group has been engaged for a decade in facilitating collective learning for UHC through a range of modalities at global, regional and national levels. We present some of our experience and draw lessons for countries and international actors interested in strengthening national systemic learning capacities for UHC. The main lesson is that with appropriate collective intelligence processes, digital tools and facilitation capacities, countries and international agencies can mobilise the many actors with knowledge relevant to the design, implementation and evaluation of UHC policies. However, really building learning health systems will take more time and commitment. Each country will have to invest substantively in developing its specific learning systemic capacities, with an active programme of work addressing supportive leadership, organisational culture and knowledge management processes.